Treatment and repair and regeneration method of waste lithium secondary battery positive electrode material
Through borohydride-assisted heat treatment and water vapor-assisted heat treatment, combined with temperature control, lithium and transition metals in the cathode material of waste lithium-ion batteries are separated and modified, which solves the problems of unsatisfactory element separation selectivity and relatively large waste output in the prior art, and realizes the regeneration of high-performance cathode active materials.
Patent Information
- Application Number
- CN202311026567.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-08-15
AI Technical Summary
In the prior art, the recycling of the cathode material of waste lithium-ion batteries has problems such as unsatisfactory element separation selectivity, difficulty in convenient regeneration of high-performance materials, and relatively large waste output.
The first stage of heat treatment assisted by borohydride and the second stage of heat treatment assisted by water vapor are used, combined with the combined control of temperature, the lattice structure of the waste cathode material is destroyed, lithium and transition metal are separated, and high-performance cathode active material is obtained through oxidation and baking repair and regeneration.
It realizes efficient separation and modification of lithium and transition metals, improves the electrochemical performance of the regenerated materials, and solves problems such as unsatisfactory element separation selectivity and relatively three waste output.
Smart Images

Figure CN117080600B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery waste recycling, and specifically relates to the field of waste lithium battery material recycling. Background Art
[0002] Waste lithium-ion batteries such as mainstream waste ternary batteries (positive electrode active materials are mainly NCM ternary materials, LiNi x Co y Mn z O2, which has a higher potential value, has a higher recovery and regeneration value.
[0003] In the existing technology, the mainstream recycling process of waste lithium-ion batteries mainly includes full acid leaching, lithium pre-extraction and other processes:
[0004] For example, a Chinese patent document with publication number CN116417704A discloses a method for recovering positive electrode materials of ternary lithium batteries based on supercritical hydrothermal reaction, which includes the following steps: first, mixing the positive electrode plates of the waste ternary lithium batteries with a first oxidant and deionized water, and performing a hydrothermal oxidation reaction under a supercritical state, and filtering to obtain a filter residue after the reaction is complete; then, acid leaching the filter residue with an inorganic acid solution containing a reducing agent, and precipitating and removing aluminum ions; then, adding nickel salt, manganese salt and cobalt salt to the aluminum removal filtrate, adjusting the ratio, and then adding a chelating agent and a precipitating agent for a co-precipitation reaction to obtain a ternary precursor; finally, after the ternary precursor has undergone a hydrothermal crystallization reaction, it is mixed with a lithium source and a second oxidant, and a hydrothermal synthesis reaction is performed under a supercritical state to obtain a regenerated ternary positive electrode material.
[0005] Another example is a Chinese patent document with publication number CN114956130A, which discloses a subcritical lithium pre-extraction method for waste lithium battery positive electrode materials. The method comprises heating a mixed solution containing waste lithium battery positive electrode powder, water and polyhydric alcohol to make the water therein in a subcritical state, maintaining the mixed solution in the subcritical state, performing lithium pre-extraction treatment, and obtaining a lithium extraction solution by solid-liquid separation after the treatment is completed; the number of alcoholic hydroxyl groups in the polyhydric alcohol is greater than or equal to 2; and the volume fraction of the polyhydric alcohol in the water and the polyhydric alcohol is greater than or equal to 30%.
[0006] Although many methods for recycling waste positive electrode materials have been reported in the prior art and have brought good recycling effects, there are still common problems such as unsatisfactory element separation selectivity, difficulty in conveniently regenerating to obtain high-performance materials, and high output of three wastes. Summary of the invention
[0007] In view of the problems faced by the existing recycling of waste lithium-ion battery positive electrodes, the purpose of the present invention is to provide a method for treating waste lithium secondary battery positive electrode materials, aiming to efficiently recover and separate lithium and transition metals from waste positive electrode materials.
[0008] The second purpose of the present invention is to provide a method for repairing and regenerating waste positive electrode materials, aiming to utilize waste positive electrode materials to regenerate high-performance positive electrode active materials.
[0009] A method for treating waste lithium secondary battery positive electrode materials comprises obtaining waste positive electrode materials from waste lithium secondary batteries, placing the waste positive electrode materials and borohydride in a reactor, and preliminarily performing a first stage heat treatment at a temperature of 400-500°C, and then performing a second stage heat treatment at a temperature of 500-600°C in a water vapor atmosphere; then performing a water immersion treatment, and performing solid-liquid separation to obtain lithium liquid and transition metal slag.
[0010] The innovative research of the present invention shows that the use of a first-stage heat treatment assisted by borohydride and a second-stage heat treatment assisted by water vapor, further coordinated with the joint control of the heat treatment temperature, can effectively destroy the lattice structure of the waste positive electrode material and effectively separate the lithium and transition metals therein. Not only that, it can also help to modify the separated components, thereby helping to improve the electrochemical properties of the regenerated material.
[0011] In the present invention, the waste lithium secondary battery may be a waste lithium ion battery.
[0012] In the present invention, the waste positive electrode material can be obtained by stripping from waste lithium secondary batteries based on known methods. For example, waste lithium ion batteries are discharged, disassembled, and stripped (such as stripping with an organic solvent NMP) to obtain waste positive electrode powder. In the present invention, considering the simplicity of the process, the waste lithium ion battery positive electrode material is also allowed to contain at least one of a conductive agent, a binder, and an electrolyte.
[0013] In the present invention, there is no special requirement for the content of waste positive electrode materials. Considering the economic efficiency of the process, the content of the active material is preferably above 50wt.%, more preferably above 80wt.%, and further preferably 80-95wt.%.
[0014] In the present invention, the borohydride is at least one of sodium borohydride and potassium borohydride.
[0015] In the present invention, the weight ratio of borohydride to the positive electrode active material in the waste positive electrode material is 5 to 10:1.
[0016] In the present invention, the waste positive electrode material and the borohydride are arranged in the reactor in a single-layer mixed or double-layer stacked manner.
[0017] The single-layer mixing method refers to that the waste positive electrode material and the borohydride are arranged in the reactor in a single-layer manner in the form of a mixture.
[0018] The double-layer stack includes a bottom layer and an upper layer arranged on the bottom layer, and the bottom layer and the upper layer are provided with a copper mesh (the holes of the copper mesh are breathable and can intercept particles in the upper layer); the bottom layer is a borohydride layer, and the upper layer is a mixed layer of waste positive electrode materials and borohydride, and the borohydride content in the upper layer accounts for 10 to 20% of the total borohydride content.
[0019] The present invention unexpectedly discovered that the use of the double-layer stacking arrangement of the components and the reaction can unexpectedly further improve the separation of lithium and transition metals, and can further improve the modification effect of the material, which helps to further improve the electrochemical properties of the regenerated material.
[0020] In the present invention, the pressure at the initial stage of the first heat treatment can be normal pressure or pressurized by a protective atmosphere; the preferred pressurized pressure is 1 to 3 MPa.
[0021] The study unexpectedly found that the use of the protective atmosphere for pressurization in the initial stage, combined with the subsequent two-stage treatment, can help further improve the separation of lithium and transition metals and the modification effect, which can further facilitate the regeneration of materials with high electrochemical properties.
[0022] Preferably, the first heat treatment lasts for 1 to 3 hours.
[0023] In the present invention, in the second treatment stage, other water vapor can be directly introduced into the treatment system, or water can be introduced into the system.
[0024] In the present invention, the amount of water vapor introduced and the weight ratio are 10 to 20:1 of the positive electrode active material in the waste positive electrode material;
[0025] Preferably, the second heat treatment lasts for 1 to 3 hours.
[0026] The present invention also provides a method for repairing and regenerating waste positive electrode materials, wherein lithium liquid and transition metal slag are obtained by the method described in the present invention; a lithium source is obtained from the lithium liquid, and then the lithium source is mixed with the transition metal slag for oxidative roasting to obtain a regenerated positive electrode active material.
[0027] The present invention has been found that, thanks to the treatment method, separation of lithium and transition metals can be achieved, and repair and modification can also be achieved. Oxidative roasting of the obtained lithium source and transition metal source can help improve the electrochemical properties of the repaired material.
[0028] In the present invention, lithium spheres and transition metal sources can be obtained by using known processes, and then they can be regenerated to form positive electrode active materials based on known processes.
[0029] In the present invention, the lithium liquid is subjected to evaporation treatment to obtain the lithium source, or the lithium liquid is subjected to carbonization precipitation treatment to obtain the lithium source. The present invention's research shows that the use of carbonization precipitation to obtain the lithium source helps to effectively retain the modification advantages of the treatment method of the present invention, and helps to further improve the electrochemical properties of the regenerated material.
[0030] In the present invention, the transition metal slag is pre-washed. Preferably, the washing process includes water washing and / or alkali washing, and more preferably includes alkali washing and water washing; more preferably, it is a process of first water washing, then alkali washing, and then water washing. Studies have found that based on this process, the modification advantages of the recycling process of the present invention can be further retained, and the electrochemical properties of the regenerated material can be further improved.
[0031] In the present invention, there is no particular requirement for the liquid-to-solid ratio in the water washing and alkali washing stages, and for example, it can be 5 to 50 ml / g. In the present invention, the alkali solution in the alkali washing stage can be a 0.1 to 5M alkali metal hydroxide aqueous solution.
[0032] In the present invention, the oxidation roasting stage is carried out in an oxygen-containing atmosphere, and the oxidation roasting temperature is 600-800°C.
[0033] Preferably, the oxidative roasting time is 1 to 5 hours.
[0034] Beneficial Effects
[0035] The innovative research of the present invention shows that the use of a first-stage heat treatment assisted by borohydride and a second-stage heat treatment assisted by water vapor, further coordinated with the joint control of the temperature of the heat treatment, can effectively destroy the lattice structure of the waste positive electrode material and can effectively separate the lithium and transition metals therein. Not only that, it can also help to modify the separated components, thereby helping to improve the electrochemical properties of the regenerated material.
[0036] The present invention adopts the two-layer stacking and one-stage heat treatment method, and further cooperates with the method of obtaining the lithium source and the transition metal source to further synergistically improve the electrochemical performance of the regenerated active material. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is the cycle diagram of Example 1; DETAILED DESCRIPTION
[0038] The present invention will be further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0039] In the present invention, there is no special requirement for the content of active material in the waste lithium-ion battery positive electrode material. Considering the economic efficiency of the process, the content is preferably above 50wt.%. In the following cases, unless otherwise stated, the active content is 85-90wt.%.
[0040] During the operation of the present invention, unless otherwise specified, such as during the washing process, the temperature is room temperature, for example, 15 to 40°C.
[0041] Embodiment 1:
[0042] Step (1):
[0043] The waste power NCM111 nickel cobalt manganese oxide lithium battery was placed in 2 mol / L salt water for 30 hours of discharge treatment, the discharged battery was dried at 85°C, the positive electrode sheet and the negative electrode sheet were disassembled and separated, the positive electrode sheet was immersed in N-methylpyrrolidone, the current collector in the electrode sheet was separated, and the waste positive electrode powder was obtained by filtering, washing and drying;
[0044] Step (2): Two-stage roasting
[0045] The waste positive electrode powder and sodium borohydride (wherein the weight ratio of NCM active material / NaBH4 is 1:7) are evenly mixed and placed in a pressure-resistant reactor for a first-stage calcination treatment, wherein the temperature of the first-stage calcination treatment (marked as T1) is 450°C and the time is 2h;
[0046] Then, water vapor (15 times the weight of the active material of the waste positive electrode powder) was introduced into the reaction system for the second stage of calcination, the temperature of this process (marked as T2) was 550°C, the time was 1 hour, and water vapor was introduced. After the reaction was completed, it was cooled to room temperature and then taken out.
[0047] Step (3):
[0048] The reaction material of step (2) is added to pure water at a liquid-to-solid ratio of 10:1 mL / g and leached at 30°C for 1 h, followed by filtration to obtain filtrate A and filter residue, the filter residue is washed with water (liquid-to-solid ratio of 15 ml / g) to obtain wash liquid a and wash residue, the washed residue is alkali washed (washed with 0.5 M sodium hydroxide alkali solution, liquid-to-solid ratio of 15 ml / g), and then washed with water until the filtrate is neutral to obtain a transition metal source;
[0049] The water washing liquid a and the filtrate A are combined to obtain a lithium solution; the lithium solution is evaporated to obtain a lithium source.
[0050] The lithium recovery rate in the waste nickel cobalt manganese oxide positive electrode is Li99.1%.
[0051] Step (4): Regeneration
[0052] The lithium source and transition metal source of step (3) are mixed, and the molar ratio of NCM is controlled to be 1:1:1, and the molar ratio of Li:NCM is controlled to be 1.05:1, and then calcined at 700°C for 3h in an air atmosphere to obtain a regenerated positive electrode active material.
[0053] The electrochemical performance of the recycled material was tested in the following steps and conditions: in a glove box under argon atmosphere, aluminum foil was used as the current collector, a positive electrode sheet containing 90% recycled positive electrode active material (recycled positive electrode active material: conductive carbon black: PVDF weight ratio is 90:5:5) was coated, the negative electrode was a lithium sheet, 1 mol / L LiPF6 EC / EMC (volume ratio 1:1) was used as the electrolyte, and at room temperature, 1C constant current cycle 500 cycles showed 178 mAh g -1 Cycle specific capacity.
[0054] Example 2
[0055] Compared with Example 1, the only difference is that the ratio of waste positive electrode powder to sodium borohydride in step (2) is changed. The experimental groups are:
[0056] A: The ratio of active material to sodium borohydride in waste positive electrode powder is 1:5;
[0057] B: The ratio of active material to sodium borohydride in waste positive electrode powder is 1:10;
[0058] Tested according to the method of Example 1, the results are:
[0059] Group A: Step (3), the lithium leaching rate is Li99.8%. At room temperature, the 1C constant current cycle shows a cycle capacity of 175 mAh g-1 in 500 cycles;
[0060] Group B: Step (3), the lithium leaching rate is Li99.9%. At room temperature, the 1C constant current cycle shows a cycle capacity of 181 mAh g-1 in 500 cycles;
[0061] Example 3
[0062] Compared with Example 1, the only difference is that the treatment mechanism of the second stage is changed, and the experimental groups are:
[0063] A: The temperature of T1 is 400℃ and the time is 3h, and the temperature of T2 is 500℃ and the time is 3h.
[0064] B: The temperature of T1 is 500℃, the time is 1h, the temperature of T2 is 600℃, the time is 1h.
[0065] Tested according to the method of Example 1, the results are:
[0066] Group A: Step (3), the lithium leaching rate is Li99.8%. At room temperature, 1C constant current cycle 500 cycles showed a cycle capacity of 183 mAh g-1;
[0067] Group B: Step (3), the lithium leaching rate was 99.8%. The cycle capacity was 179 mAh g-1 in 500 cycles at 1C constant current at room temperature.
[0068] Example 4
[0069] Compared with Example 1, the only difference is that in step (2), the initial stage of the first stage of calcination is changed to pre-pressurize to 1 MPa with Ar, and then the temperature is raised to T1 for calcination. The temperature of the water immersion process is 20°C, and the subsequent stages are the same as in Example 1.
[0070] Tested according to the method of Example 1, the results are:
[0071] In step (3), the lithium leaching rate is 99.8%. The cyclic capacity of the product is 195 mAh g-1 in 500 cycles at 1C constant current at room temperature.
[0072] Example 5
[0073] Compared with Example 1, the only difference is that in step (2), a double-layer stacking method is used for sample setting: 85% of sodium borohydride is set at the bottom layer of the reactor, and the active material in the waste positive electrode powder and the remaining 15% of the sodium borohydride mixture are set at the upper layer of the stratum, and the bottom layer and the upper layer are provided with copper mesh; the mesh holes of the copper mesh are air-permeable and can intercept the upper layer particles. The temperature of the water immersion process is 20°C, and other operations and parameters are the same as in Example 1.
[0074] Tested according to the method of Example 1, the results are:
[0075] In step (3), the lithium leaching rate is 99.9%. The specific capacity of the filtrate is 196 mAh g-1 in 500 cycles at 1C constant current at room temperature.
[0076] Example 6
[0077] Compared with Example 5, the only difference is that in step (3), carbon dioxide is introduced into the lithium liquid until precipitation is completed, and the solid-liquid separation is performed to obtain the lithium source; the subsequent steps are the same as in Example 1.
[0078] Tested according to the method of Example 1, the results are:
[0079] At room temperature, the cyclic specific capacity of the battery was 197 mAh g-1 after 500 cycles at 1C constant current.
[0080] Comparative Example 1
[0081] Compared with Example 1, the only difference is that the first heat treatment process is carried out in a mixed gas containing 10 vol% of hydrogen-Ar. Other operations and parameters are the same as in Example 1.
[0082] The lithium recovery rate of the waste nickel-cobalt-manganese-oxide positive electrode was 98.8%, and the regenerated active material had a cycle specific capacity of only 157 mAh g-1 after 200 cycles under the conditions of Example 1.
[0083] Comparative Example 2
[0084] Compared with Example 1, the only difference is that NaBH4 is not added in the first calcination stage, and other operations and parameters are the same as Example 1.
[0085] The test was carried out according to the method of Example 1. The results showed that the lithium recovery rate was 47.9%, and the regenerated active material had only 113 mAh g after 200 cycles according to the conditions of Example 1. -1 Cycle specific capacity.
[0086] Comparative Example 3
[0087] Compared with Example 1, the only difference is that water vapor is not introduced in the second roasting stage, and other operations and parameters are the same as Example 1.
[0088] The test was carried out according to the method of Example 1. The results were as follows: the lithium recovery rate was 98.5%, and the regenerated active material had a cycle specific capacity of only 166 mAh g-1 after 200 cycles under the conditions of Example 1.
[0089] Comparative Example 4
[0090] Compared with Example 1, the only difference is that the temperature of the first stage roasting is changed to 300° C., and the other operations and parameters are the same as Example 1.
[0091] The lithium leaching rate in the waste nickel-cobalt-manganese-oxide positive electrode is Li64.3%, and the regenerated active material has a cycle specific capacity of only 156 mAh g-1 after 200 cycles under the conditions of Example 1.
Claims
1. A method for treating waste lithium secondary battery positive electrode materials, characterized in that: Obtaining waste positive electrode materials from waste lithium secondary batteries, placing the waste positive electrode materials and borohydride in a reactor, and preliminarily performing a first heat treatment at a temperature of 400-500° C., and then performing a second heat treatment at a temperature of 500-600° C. in a water vapor atmosphere; then performing a water immersion treatment, and filtering to obtain lithium liquid and transition metal slag; The waste lithium secondary battery is a waste lithium ion battery; the positive electrode active material contained in the waste positive electrode material includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, and nickel-cobalt-manganese ternary.
2. The processing method according to claim 1, characterized in that: The waste positive electrode material also includes at least one of a separator, a conductive agent, a binder and an electrolyte.
3. The processing method according to claim 2, characterized in that: The content of positive electrode active material in the waste positive electrode material is above 50wt%.
4. The processing method according to claim 3, characterized in that: The content of positive electrode active material in the waste positive electrode material is 80-95wt.%.
5. The processing method according to claim 1, characterized in that: The borohydride is at least one of sodium borohydride and potassium borohydride.
6. The processing method according to claim 1, characterized in that: The weight ratio of borohydride to the positive electrode active material in the waste positive electrode material is 5~10:
1.
7. The processing method according to any one of claims 1 to 6, characterized in that: The waste positive electrode material and the borohydride are arranged in a reactor in a single-layer mixed or double-layer stacked manner; The double-layer stack includes a bottom layer and an upper layer arranged on the bottom layer, and the bottom layer and the upper layer are provided with copper mesh; the bottom layer is a borohydride layer, the upper layer is a mixed layer of waste positive electrode material and borohydride, and the borohydride content in the upper layer accounts for 10-20% of the total borohydride content.
8. The processing method according to claim 1, characterized in that: The first heat treatment is initially performed by pressurizing the chamber with a protective atmosphere.
9. The processing method according to claim 8, characterized in that: The pressure of the first stage heat treatment is 1~3MPa.
10. The processing method according to claim 8, characterized in that: The first heat treatment time is 1~3h.
11. The processing method according to claim 1, characterized in that: In the second treatment stage, the amount of water vapor introduced is 10~20:1 of the weight of the positive electrode active material in the waste positive electrode material.
12. The processing method according to claim 1, characterized in that: The second heat treatment time is 1~3h.
13. A method for repairing and regenerating waste positive electrode materials, characterized in that: A lithium liquid and transition metal slag are obtained by the treatment method according to any one of claims 1 to 12; a lithium source is obtained from the lithium liquid, and then the lithium source is mixed with the transition metal slag for oxidative roasting to obtain a regenerated positive electrode active material.
14. The method for repairing and regenerating waste positive electrode materials according to claim 13, characterized in that: The lithium liquid is subjected to evaporation treatment to obtain a lithium source, or the lithium liquid is subjected to carbonization precipitation treatment to obtain a lithium source.
15. The method for repairing and regenerating waste positive electrode materials according to claim 13, characterized in that: The transition metal slag is washed in advance.
16. The method for repairing and regenerating waste positive electrode materials according to claim 15, characterized in that: The washing includes water washing and / or alkali washing process.
17. The method for repairing and regenerating waste positive electrode materials according to any one of claims 13 to 16, characterized in that: The temperature of the oxidation roasting stage is 600~800℃.
Citation Information
Patent Citations
Subcritical lithium pre-extraction method of waste lithium battery positive electrode material
CN114956130A
Ternary lithium battery positive electrode material recovery method based on supercritical hydrothermal reaction
CN116417704A
Recycling method of nickel-hydrogen secondary battery
US6077622A
KR1017081490000B1